1990
DOI: 10.1080/03075079012331377471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of student learning. I—An unfolding analysis of the association between perceptions of learning context and approaches to studying at an individual level

Abstract: This study investigates the association between students" perceptions of learning context and approaches to studying at an individual level. The emphasis of this study thus focuses on individual student differences and, in order to facilitate the analyses presented, a statistical procedure (multidimensional unfolding analysis) has been introduced that is new to educational research of this nature. This procedure is described in non-technical terms as well as in a more technical Appendix. The results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 17 publications
(13 reference statements)
4
69
0
2
Order By: Relevance
“…Meyer and Muller (1990) identified associations between students' perceptions of the learning context and their approaches to studying in terms of deep/achieving and surface/reproducing aspects of learning. The use of discrete categories to conceptualise approaches to study however has psychometric limitations.…”
Section: Introductionmentioning
confidence: 98%
“…Meyer and Muller (1990) identified associations between students' perceptions of the learning context and their approaches to studying in terms of deep/achieving and surface/reproducing aspects of learning. The use of discrete categories to conceptualise approaches to study however has psychometric limitations.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have investigated and reported differential forms of learning behaviour on the basis of purely empirical evidence (Meyer and Muller 1990) as well as interview data (Meyer 1991, Parsons 1992, Cliff 1992) and have formulated a categorical basis for distinguishing between them , Meyer 1991. More recently, an exhaustive categorisation procedure has been proposed that can be applied to inventory response data and executed by means of programmable logic (Meyer 1994).…”
Section: Qualitatively Contrasting Forms Of Learning Behaviourmentioning
confidence: 97%
“…The categofisation procedure treats ASI subscale responses as preference structures determined, for each individual, on the basis of a normalised ranking of the response score variables (Meyer and Muller 1990). Each such individual structure is then examined (on a true/false basis) for embedded features that can conceptually be used as a basis for risk categorisation.…”
Section: Qualitatively Contrasting Forms Of Learning Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Die navorsingsontwerp word vervolgens onder die loep geneem. Die studente in die Departement Elektriese en Siviele Ingenieurswese is vervolgens op grond van 'n gestratifiseerde, ewekansige steekproef in twee groepe elk (eksperimentele groep en kontrolegroepe) verdeel.…”
unclassified